2017
DOI: 10.2337/dc16-2765
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Environmental Exposures to Endocrine-Disrupting Chemicals and Diabetes Risk in Vulnerable Populations

Abstract: Burgeoning epidemiological, animal, and cellular data link environmental endocrine-disrupting chemicals (EDCs) to metabolic dysfunction. Disproportionate exposure to diabetes-associated EDCs may be an underappreciated contributor to disparities in metabolic disease risk. The burden of diabetes is not uniformly borne by American society; rather, this disease disproportionately affects certain populations, including African Americans, Latinos, and low-income individuals. The purpose of this study was to review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 91 publications
3
116
0
3
Order By: Relevance
“…Poverty is associated with fatalism, dependency, need for governmental aid, drug and alcohol use, stresses on family life, low self-esteem, community disengagement, increased risk for disease and complications, and decreased access to quality health care, but also gaps in formal populationspecific recommendations (4,161). Moreover, there are environmental inequalities or disparities in exposure to endocrine-disrupting compounds (endocrine discrupting chemicals or EDCs; polychlorinated biphenyls, organochlorine pesticides, air pollutants, bisphenol A, and phthalates) (162). This socio-economic correlate involving EDCs affects diabetes prevalence rates (162).…”
Section: Behavior and Social Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty is associated with fatalism, dependency, need for governmental aid, drug and alcohol use, stresses on family life, low self-esteem, community disengagement, increased risk for disease and complications, and decreased access to quality health care, but also gaps in formal populationspecific recommendations (4,161). Moreover, there are environmental inequalities or disparities in exposure to endocrine-disrupting compounds (endocrine discrupting chemicals or EDCs; polychlorinated biphenyls, organochlorine pesticides, air pollutants, bisphenol A, and phthalates) (162). This socio-economic correlate involving EDCs affects diabetes prevalence rates (162).…”
Section: Behavior and Social Determinantsmentioning
confidence: 99%
“…Moreover, there are environmental inequalities or disparities in exposure to endocrine-disrupting compounds (endocrine discrupting chemicals or EDCs; polychlorinated biphenyls, organochlorine pesticides, air pollutants, bisphenol A, and phthalates) (162). This socio-economic correlate involving EDCs affects diabetes prevalence rates (162).…”
Section: Behavior and Social Determinantsmentioning
confidence: 99%
“…A number of these measures have been associated with diabetes risk and outcomes (reviewed in Ref. [9••]). For example, some studies have demonstrated that increased exposure to fine particulate matter (PM 2.5 ) is associated with dynamic changes in insulin resistance [10, 11] and prevalent diabetes [12, 13].…”
Section: Environmental Exposures and Diabetesmentioning
confidence: 99%
“…Similarly, individuals with lower incomes and less education are more likely to have diabetes [57]. While several factors have been proposed to contribute to these differences [37], a recent analysis suggests that differential exposures to diabetes-promoting EDCs may contribute to disease disparities among African Americans, Hispanics, and those with low incomes [9••].…”
Section: Diabetes Disparities and Environmental Justicementioning
confidence: 99%
“…A mechanistic understanding of racial disparities in disease therefore requires a characterization of differences in environmental risk factors. In particular, differences in chemical exposures have been hypothesized to be important etiologic factors in racial disparities of disease rates (Hoover et al 2012; Juarez and Matthews-Juarez 2018; Ruiz et al 2018; Wang et al 2016; Zota and Shamasunder 2017).…”
Section: Introductionmentioning
confidence: 99%